Transcriptional Profiling of Human Epithelial Cells Infected with Plasmid-Bearing and Plasmid-Deficient Chlamydia trachomatis - Porcella, Stephen F. (Infect Immun, 2015)
Chlamydia trachomatis is an obligate intracellular epitheliotropic bacterial pathogen of humans. Infection of the eye can result in trachoma, the leading cause of preventable blindness in the world. The pathophysiology of blinding trachoma is driven by multiple episodes of reinfection of conjunctival epithelial cells, producing an intense chronic inflammatory response resulting in submucosal tissue remodeling and scarring. Recent reports have shown that infection with trachoma organisms lacking the cryptic chlamydial plasmid is highly attenuated in macaque eyes, a relevant experimental model of human trachoma infection. To better understand the molecular basis of plasmid-mediated infection attenuation and the potential modulation of host immunity, we conducted transcriptional profiling of human epithelial cells infected with C. trachomatis plasmid-bearing (A2497) and plasmid-deficient (A2497P(−)) organisms. Infection of human epithelial cells with either strain increased the expression of host genes coding for proinflammatory (granulocyte-macrophage colony-stimulating factor [GM-CSF], macrophage colony-stimulating factor [MCSF], interleukin-6 [IL-6], IL-8, IL-1α, CXCL1, CXCL2, CXCL3, intercellular adhesion molecule 1 [ICAM1]), chemoattraction (CCL20, CCL5, CXCL10), immune suppression (PD-L1, NFKB1B, TNFAIP3, CGB), apoptosis (CASP9, FAS, IL-24), and cell growth and fibrosis (EGR1 and IL-20) proteins. Statistically significant increases in the levels of expression of many of these genes were found in A2497-infected cells compared to the levels of expression in A2497P(−)-infected cells. Our findings suggest that the chlamydial plasmid plays a focal role in the host cell inflammatory response to infection and immune avoidance. These results provide new insights into the role of the chlamydial plasmid as a chlamydial virulence factor and its contributions to trachoma pathogenesis.